Treaty negotiation, drafting, ratification and accession by Caricom States. - ROBINSON, Patrick (1993)
Comments on the preparatory stage before treaty negotiation. Distinguishes between bilateral and multilateral treaties and highlights the dichotomy in negotiating positions at the bilateral and multilateral levels. Emphasises the interrelationship between treaty drafting and treaty negotiation. Is of the view that the Caribbean could benefit from carefully considered legislation dealing with treaty making power.